ESKALASI PROGRAM ALUR MERDEKA MATERI ETNOSAINS PEMBUATAN KLEPON DALAM ESKALASI LITERASI SAINS PADA MATA KULIAH PRAKTIKUM IPA PGSD FKIP UMSU - Sari, Suci Perwita; Nasution, Ismail Saleh; Sari, Mawar (JURNAL TARBIYAH, 2023)
The background of this program evaluation is the urgent of learning loss due to Covid-19 which calls for learning to be carried out online. By this Alur Merdeka Program, it is hoped that it will be an escalation/improvement of scientific literacy in natural science practicum courses for PGSD FKIP UMSU students. The evaluation method for the Merdeka flow program in scientific literacy escalation and the evaluation results of the implementation of the Merdeka flow evaluation program in scientific literacy escalation in the Science practicum course at PGSD FKIP UMSU in terms of context, input, process, and product. The results of this study are that at the content evaluation stage an analysis of the needs of students, lecturers and learning outcomes is carried out. In the input evaluation step, the validation stage was carried out which resulted in 96.7% of the material being declared valid, 89.3% of the design being declared valid, and 84% of the language being declared valid in the development of learning tools. In the process evaluation step it was stated that in the application of the independent groove there was a change in each of the students' scientific literacy indicators in using the independent groove. students' scientific literacy in channel 1 has increased compared to pre-stream. Where in explaining the phenomenon there is an increase from an average of 75.4 to 89.23. The indicators evaluating and designing scientific investigations increased from 78.6 to 90 and the indicators interpreting data increased from an average of 75 to 91. In the final stage, namely product evaluation, it was stated that the learning tools used